Instituição de Longa Permanência Mieroik : Instituição de Longa Permanência Para Idosos - Souza, Aline Farias (Brasil, 2025)
Although the elderly population is growing, society is still not fully prepared to address the physical and mental health needs of seniors. This project proposes the design of a Long-Term Care Facility for Elderly Victims of Violence, focusing on accessibility and a sense of community to enhance the quality of life for the residents. The proposal was developed based on bibliographic research, reference studies, and analysis of project requirements, culminating in a justification report. The facility will be located on an 11,000 m² lot in São Geraldo. The needs program is divided into five sectors on the ground floor to ensure full accessibility, interconnected by gardens. The project emphasizes community integration and aims to avoid social segregation.